Collaborate with registrars to ensure quality FERPA training. (February 2015) - Rainsberger, Richard
<x xml:space="preserve">Abstract</x> Many higher ed officials lack the knowledge needed to properly apply the Family Educational Rights and Privacy Act regulations in day‐to‐day professional situations.